Confronting The Challenges Encountered By Primary School Teachers In The Use Of Technological Devices For Teaching - Alfred, Dakoru Osomkume; Idoghor, Uduak (Advances in Social Sciences Research Journal, 2020)
The paper examined the objectives of primary education in Nigeria as stated in the National Policy on Education. These objectives are seen to be achievable only through the instrumentally of the teachers who are the primary implementers of the curriculum. Furthermore, who a teacher is was also critically examined. In addition, the paper advanced some inevitable qualities of a 21st century teacher, without which the teacher will become a misfit in the classroom. These include having a sound knowledge (mastery) of the his/her subject-matter, being properly trained to teach, openness to innovation, being an in-co-parentis, resourcefulness and being computerate. The importance of the application or integration of technologies in the 21st century was also indicated. The climax of the content of the paper was the challenges facing primary school teachers, especially those in the rural areas. The challenges facing Primary School teachers as advanced include ignorance, technophobia, incomputeracy among others. Finally, recommendations on how to confront these challenges were advanced. Some of which are that teachers should wake up to the challenges of the 21st century by making sure that they get trained, the government should also make provision for teachers to get trained and be retrained, teachers should be given certain incentives to encourage them among others